Net production of Atlantic salmon (FIFO, Fish in Fish out < 1) with dietary plant proteins and vegetable oils. (5th June 2012) - Liland, N.S.; Rosenlund, G.; Berntssen, M.H.G.; Brattelid, T.; Madsen, L.; Torstensen, B.E.
Abstract Adult Atlantic salmon (Salmo salar; approximately 800 g start weight) were fed diets with a high replacement of fish meal (FM) with plant proteins (70% replacement), and either fish oil (FO) or 80% of the FO replaced by olive oil (OO), rapeseed oil (RO) or soybean oil (SO) during 28 weeks in triplicate. Varying the lipid source only gave non‐significant effects on growth and final weight. However, a significantly reduced feed intake was observed in the SO fed fish, and both feed utilization and lipid digestibility were significantly reduced in the FO fed fish. Limited levels of dietary 18:3n‐3, precursor to EPA and DHA, resulted in no net production of EPA and DHA despite increased mRNA expression of delta‐5‐desaturase and delta‐6‐desaturase in all vegetable oil fed fish. Net production of marine protein, but not of marine omega‐3 fatty acids, is thus possible in Atlantic salmon fed 80% dietary vegetable oil and 70% plant proteins resulting in an estimated net production of 1.3 kg Atlantic salmon protein from 1 kg of FM protein. Production of one 1 kg of Atlantic salmon on this diet required only 800 g of wild fish resources (Fish in ‐ Fish out < 1).